Responding to the COVID-19 outbreak as a therapeutic community in a forensic psychiatric ward in Japan–A reconsideration of the role of therapeutic community in disasters - Kashiwagi, Hiroko; Kume, Kayo; Takeda, Koji; Ueshima, Taiki; Asaumi, Osamu; Omori, Mayu; Hirabayashi, Naotsugu (Frontiers in Psychiatry, 2022)
The global impact of COVID-19 outbreak on psychiatric hospitals and prisons is unfathomable and unprecedented, and information is needed on how best to mitigate widespread infection whilst safeguarding the community’s wellbeing. This study reports on how the staff and patients in a forensic psychiatric ward in Japan worked together during the COVID-19 outbreak as a ‘therapeutic community.’ The “Non-Three Cs” Karaoke Project, with infection prevention guidelines designed by inpatients, was safely conducted and its humour released the staff and patients’ anxiety and tension. Through these discussions, the patients and staff gained a better understanding of viruses, transmission routes, countermeasures, and coping with stress. The study highlights the importance of disclosing information to inpatients, conducting open discussions, and involving patients in the prevention and management of infectious diseases. This report is the world's first report showing a concrete example of the therapeutic community’s significance during the COVID-19 outbreak. It is an experience that offers an opportunity to reconsider the significance of the therapeutic community, in which patients are seen as a presence that brings change, strength, growth, and creativity into the therapeutic setting. We believe that such an approach in a future disaster would lead to an increase in the patients’ problem-solving ability, and recovery and autonomy after discharge could be promoted. A shared difficult situation can be an opportunity to build a therapeutic alliance and make a difference.